2021
DOI: 10.2196/25357
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Web-Based Patient Education Materials on Transarterial Chemoembolization: Systematic Review

Abstract: Background Thousands of web searches are performed related to transarterial chemoembolization (TACE), given its palliative role in the treatment of liver cancer. Objective This study aims to assess the reliability, quality, completeness, readability, understandability, and actionability of websites that provide information on TACE for patients. Methods The five most popular keywords pertaining to TACE were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
6
0
4
Order By: Relevance
“…Relationship to previous studies -Our study methodology on analysis of information contained in online videos is similar in initially establishing search criteria, using multiple reviewers and a validated tool (PEMAT). 23,24 Several studies have found information content in online videos for various medical conditions to lack reliability, not of high quality, to be at a higher reading level than recommended and not meet the needs of patients. 25,26,27,28,29 In contrast, we assessed content from a perspective of shared decision making (SDM) and identify areas to target for improving quality of online videos.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship to previous studies -Our study methodology on analysis of information contained in online videos is similar in initially establishing search criteria, using multiple reviewers and a validated tool (PEMAT). 23,24 Several studies have found information content in online videos for various medical conditions to lack reliability, not of high quality, to be at a higher reading level than recommended and not meet the needs of patients. 25,26,27,28,29 In contrast, we assessed content from a perspective of shared decision making (SDM) and identify areas to target for improving quality of online videos.…”
Section: Discussionmentioning
confidence: 99%
“…Moh Thesis 0 0 0 0 (Alnafea et al, 2017;Azer et al, 2018;Brütting et al, 2018;Fowler et al, 2017;Guan et al, 2018;Kasabwala et al, 2013;Santos et al, 2018;Unaka et al, 2017;Wallace & Lennon, 2004;Wallace et al, 2006;Wiriyakijja et al, 2016;Wong & Levi, 2017a, 2017bRai et al, 2021;Shamil et al, 2021;Sideris et al, 2021;Szabo et al, 2021;Ó Doinn et al, 2022;Treffalls et al, 2022).…”
Section: Readabilityunclassified
“…This criterion is evaluated using the Patient Education Materials Assessment Tool (PEMAT) (Lipari et al, 2019). This criterion was examined in fourteen studies (Abdul Rahman et al, 2020;Alwani et al, 2021;Bui et al, 2018;Gillum, 2017;Guitton, 2015;Gulbrandsen et al, 2022;Harris et al, 2018;Lamb et al, 2022;Lipari et al, 2019;Magrath et al, 2022;McClure et al, 2016;Miles et al, 2021;Sideris et al, 2021;Vishnevetsky et al, 2018;Wang et al, 2022). 9 Complexity Three criteria are used to determine the complexity of materials: structure, density, and dependency.…”
Section: Comprehensibility or Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations